Characterization of a New Hsp110 Inhibitor as a Potential Antifungal - Cancan Sun; Yi Li; Justin M. Kidd; Jizhong Han; Liangliang Ding; Aaron E. May; Lei Zhou; Qinglian Liu (Journal of Fungi)
Fungal infections present a significant global health challenge, prompting ongoing research to discover innovative antifungal agents. The 110 kDa heat shock proteins (Hsp110s) are molecular chaperones essential for maintaining cellular protein homeostasis in eukaryotes. Fungal Hsp110s have emerged as a promising target for innovative antifungal strategies. Notably, 2H stands out as a promising candidate in the endeavor to target Hsp110s and combat fungal infections. Our study reveals that 2H exhibits broad-spectrum antifungal activity, effectively disrupting the in vitro chaperone activity of Hsp110 from Candida auris and inhibiting the growth of Cryptococcus neoformans. Pharmacokinetic analysis indicates that oral administration of 2H may offer enhanced efficacy compared to intravenous delivery, emphasizing the importance of optimizing the AUC/MIC ratio for advancing its clinical therapy.